Possibilities determine the combinatorial structure of probability polytopes - Abramsky, S; Mansfield, S; Kishida, K; Lal, R; Barbosa, R (Elsevier, 2016)
We study the set of no-signalling empirical models on a measurement scenario, and show that the combinatorial structure of the no-signalling polytope is completely determined by the possibilistic information given by the support of the models. This is a special case of a general result which applies to all polytopes presented in a standard form, given by linear equations together with non-negativity constraints on the variables.